Randomized controlled comparative study of anterior abdominal field block at linea semilunaris with a standard institutional regimen for postoperative analgesia in caesarean section: Post-operative caesarean section analgesia with abdominal field block - Sudhakar D.S.; Selvakumar R.; Arunachalam R.; Murugesan K.; Karthick S. (Serbian Journal of Anesthesia and Intensive Therapy)
Introduction: A transverse abdominis plane block is a recent and newer method to reduce post-operative pain due to abdominal incisions. The efficacy of anterior abdominal field block at the linea semilunaris technique compared with a placebo. Methods: A randomized controlled comparative interventional study was conducted at Government Dharmapuri Medical College and Hospital, Dharmapuri, Tamil Nadu, India between January 2023 to June 2023. Patients recruited for the study were randomized and allotted to receive either the drug or the placebo. One of the groups received an abdominal field block with 20 ml of 0.25% bupivacaine, and the placebo group received a Normal Saline injection at the same site. A standard institutional protocol of inj. diclofenac 100 mg rectal suppository; and Inj. Tramadol 100 mg intramuscularly was followed in all the cases. Visual Analog score was used to analyse post-operative pain. If indicated, rescue analgesia - injection of tramadol 100 mg (if VAS >4) was given intramuscularly. Results: Final analysis included 40 subjects. 20 participants in treatment and placebo group; This study shows that transversus abdominis plane (TAP) done at linea semilunaris provides adequate postoperative analgesia for a shorter duration. The difference in VAS score was between the procedure group and placebo at 4 hours was significant. After this, there was no significant difference in the VAS score between the two groups. There was a significant reduction in the need for rescue analgesia at 4 hours. The hemodynamic changes in the procedure group compared to the placebo group was not significant. Conclusion: There is a significant usage for anterior approach abdominal field block (Linea semilunaris block) in providing analgesia for post-Caesarean section.